Faktor- Faktor yang Berhubungan dengan Perilaku Seksual Pranikah pada Remaja - Reggy Satrio Putro; Sunirah Sunirah; Amzal Motrin Andas; Fauziah H Wada (Jurnal Surya Medika (JSM), 2022)
Sexuality develops from childhood, adolescence to adulthood. Sexuality can be done in the form of sexual behavior. Many factors cause sexual urges, including using drugs, fantasizing about sex, watching, hearing, and viewing pornographic images. The impact that often occurs from premarital sex is very bad for health, namely the risk of contracting venereal diseases and HIV/AIDS, as well as disturbances in the reproductive organs to the occurrence of unwanted pregnancies, which will encourage abortion and the risk of social and psychological disorders. To determine the relationship between knowledge, family norms, religious norms, and smartphone use in adolescents at senior High School 1 Branchbunign Bekasi Regency. Quantitative research design with a cross-sectional design with a sample size of 166 people. The results of the study using the chi-square statistical method with a maximum value of alpha = 0.05 showing no relationship between knowledge and premarital sexual behavior with p-value = 0.036 > alpha = 0.05 and there is no relationship between family norms and premarital sexual behavior with a p-value value = 0.365 > alpha = 0.05 and there is no relationship between religious norms and premarital sexual behavior with p-value = 1.000 > alpha = 0.05 and there is no relationship between smartphone use and premarital sexual behavior with p-value = 1.000 > alpha = 0.05. Adolescents in high school were at the highest risk of premarital sexual behavior.